Validade, confiabilidade, consistência interna e efeito chão e teto do World Health Organization Disability Assessment Schedule (WHODAS) 2.0 em indivíduos com Insuficiência Cardíaca Crônica - Gondim, Georgia de Melo Castro (2023)
INTRODUCTION: Due to the manifestations caused by Chronic Heart Failure (CHF), patients' quality of life and health-related functionality are significantly compromised. WHODAS 2.0, as a generic instrument, has been used in this population, which would be more advisable if its psychometric properties were evaluated specifically for this public. OBJECTIVE: To assess internal consistency, test-retest reliability, convergent and discriminative construct validity, and floor and ceiling effect of the WHODAS 2.0 in individuals with CHF. METHODS: This is a methodological study. The sample size consisted of 100 patients with CHF treated at the Cardiology outpatient clinic of the Walter Cantídio University Hospital (WCUH). Data collection was performed in an interview that also included sociodemographic and clinical data, Charlson comorbidity index, Mini-Mental State Examination (MMSE), New York Heart Association (NYHA) functional classification, Duke Activity Status Index (DASI) and the Minnesota Living with Heart Failure Questionnaire (MLHFQ). RESULTS: The population was predominantly male (57%) and literate (84%) and the mean age was 57.8 years. WHODAS 2.0 showed good internal consistency (Cronbach's alpha >0.7 in all instrument domains), good reproducibility (ICC=0.789), moderate results in convergent construct validity, when compared to DASI and MLHFQ. In addition, it presented significant correlations of discriminative validity when correlated with the NYHA. All domains had a high floor-effect index and a low ceiling-effect index. CONCLUSION: WHODAS is a valid, consistent and reliable instrument in the population of individuals with CHF.